Fostering Agricultural Skills for Youth Livelihoods through Natural Resource Capital Generation - Pradhan, Kausik; Maity, Biman; Chigilipalli, Mounika (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during April, 2023–March, 2024 in two blocks of Cooch Behar district and two blocks of Malda district, West Bengal, India to explore the generation of natural resource capital through skill development of youth in Agriculture. From each block two villages were selected randomly. From each block, two villages were selected randomly by making a total of eight villages. An exhaustive list of youth was prepared in these villages, and from each village, 25 respondents were selected randomly through a simple random sampling procedure, making a total sample size of 200 skilled rural youth. The data were collected with the help of structured interview schedule prepared for the study through personal interview method. The data were processed with the help of the statistical tools namely frequency, percentage, mean, standard deviation, coefficient of variation, coefficient of correlation, and multiple regression. The findings emphasized that the variables land holding and youth orientation towards skill development were positively and significantly associated with the variable natural resource capital agricultural implements possession and risk ability were negatively and significantly associated with the variable natural resource capital of the skilled rural youth who were practicing agriculture. It was concluded that the critical role of targeted skill development initiatives in building natural resource capital and fostering long-term livelihood sustainability among rural youth in West Bengal.